(untitled) ("Conference on Universal Science Research 2023", 2024)
The article aims to elucidate the intricate terminologies within the realms of international and non-alternative insurance. It delves into the definitions, complexities, and significance of these terms, shedding light on their implications for individuals and businesses worldwide. Through a comprehensive exploration, it offers a deeper understanding of the nuances and differences between international and non-alternative insurance, emphasizing their role in mitigating risks on a global scale.